2012
DOI: 10.1098/rsif.2012.0535
|View full text |Cite
|
Sign up to set email alerts
|

Multiwalled carbon nanotubes in alfalfa and wheat: toxicology and uptake

Abstract: Data on the bioavailability and toxicity of carbon nanotubes (CNTs) in the environment, and, in particular, on their interactions with vascular plants, are limited. We investigated the effects of industrial-grade multiwalled CNTs (75 wt% CNTs) and their impurities on alfalfa and wheat. Phytotoxicity assays were performed during both seed germination and seedling growth. The germinations of both species were tolerant of up to 2560 mg l 21 CNTs, and root elongation was enhanced in alfalfa and wheat seedlings exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
70
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 154 publications
(72 citation statements)
references
References 60 publications
1
70
1
Order By: Relevance
“…Over last few years, there have been extensive studies to understand the influence of nanomaterials on the growth of different types of plants (Khodakovskaya et al 2009;Khodakovskaya et al 2013a, b;Lu et al 2002;Cañas et al 2008;Yang et al 2006;Hong et al 2005a, b;Tan et al 2009;Yuan et al 2011;Khodakovskaya et al 2013a, b;Mahajan et al 2011;Wang et al 2012;Larue et al 2012;Miralles et al 2012;Feizi et al 2012;Tripathi et al 2011;Sonkar et al 2012). Khodakovskaya et al (2009Khodakovskaya et al ( , 2013a demonstrated that at very low doses MWCNT can penetrate the seed coat and enhance the germination of tomato plant.…”
Section: Introductionmentioning
confidence: 99%
“…Over last few years, there have been extensive studies to understand the influence of nanomaterials on the growth of different types of plants (Khodakovskaya et al 2009;Khodakovskaya et al 2013a, b;Lu et al 2002;Cañas et al 2008;Yang et al 2006;Hong et al 2005a, b;Tan et al 2009;Yuan et al 2011;Khodakovskaya et al 2013a, b;Mahajan et al 2011;Wang et al 2012;Larue et al 2012;Miralles et al 2012;Feizi et al 2012;Tripathi et al 2011;Sonkar et al 2012). Khodakovskaya et al (2009Khodakovskaya et al ( , 2013a demonstrated that at very low doses MWCNT can penetrate the seed coat and enhance the germination of tomato plant.…”
Section: Introductionmentioning
confidence: 99%
“…For example, reduced germinated was noted with nanoparticle ZVI on Hordeum vulgare and Linum usitatissimum seeds at 250 mg/L, NP-ZnO on Zea mays seeds at 2000 mg/L, and CeO 2 on Medicago sativa, Zea mays and Cucumis sativus seeds at 2000 mg/L (Lin and Xing, 2007;LopezMoreno et al, 2010b;El-Temsah and Joner, 2012;Feizi et al, 2012;Ghafariyan et al, 2013). Compared to metal-based ENMs, CNTs were shown to not affect seed germination even at 2000 mg/L (Lin and Xing, 2007;Miralles et al, 2012a). Positive effects on seed germination were reported mainly in TiO 2 and industrial-grade CNTs, particularly on seeds with inherently low germination (Zheng et al, 2005;Miralles et al, 2012a;Feizi et al, 2013).…”
Section: General Toxicity Tests On Seeds/seedlingsmentioning
confidence: 99%
“…However, positive effects were noticed upon NP Au, Fe 2 O 3 , CeO 2 exposure over ion or bulk particle controls, including size-specific effects on root elongation (Barrena et al, 2009;Lopez-Moreno et al, 2010a;Ghodake et al, 2011;Dimkpa et al, 2012;Alidoust and Isoda, 2013;Ghafariyan et al, 2013). Conflicting data in the literature are common for carbon-based ENMs such as graphene, SWCNTs, and MWCNTs (Canas et al, 2008;Begum et al, 2011;Miralles et al, 2012a). More disconcerting than the contradictory findings in the literature is the almost complete lack of mechanistic understanding for the observed plant responses.…”
Section: General Toxicity Tests On Seeds/seedlingsmentioning
confidence: 99%
See 2 more Smart Citations